2015
DOI: 10.1027/0227-5910/a000289
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies in Adolescents Who Self-Harm

Abstract: The results support previous data regarding a different pattern of coping strategies used by adolescents who harm themselves. The use of self-rating instruments and the cross-sectional nature of the study limit our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
(55 reference statements)
0
8
0
2
Order By: Relevance
“…Drawing on the EAM, this study focuses on the psychological factors that may precede self‐harm that are well supported in past research. Psychological risk factors include depression and anxiety, low self‐esteem, impulsivity, and attention and conduct difficulties (Brunner et al., 2014; Slap, Goodman, & Huang, 2001)’ protective factors include coping strategies (Guerreiro, Figueira, Cruz, & Sampaio, 2015), meaning in life (Kleiman & Beaver, 2016) and life satisfaction (Heisel & Flett, 2004). To provide context for these psychological factors, this study includes a range of social and environmental factors: age, female gender, ethnicity, parental divorce/separation, bullying, self‐harm modelling, supportive relationships and spirituality (Brunner et al., 2014; Hawton, Saunders, & Connor, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Drawing on the EAM, this study focuses on the psychological factors that may precede self‐harm that are well supported in past research. Psychological risk factors include depression and anxiety, low self‐esteem, impulsivity, and attention and conduct difficulties (Brunner et al., 2014; Slap, Goodman, & Huang, 2001)’ protective factors include coping strategies (Guerreiro, Figueira, Cruz, & Sampaio, 2015), meaning in life (Kleiman & Beaver, 2016) and life satisfaction (Heisel & Flett, 2004). To provide context for these psychological factors, this study includes a range of social and environmental factors: age, female gender, ethnicity, parental divorce/separation, bullying, self‐harm modelling, supportive relationships and spirituality (Brunner et al., 2014; Hawton, Saunders, & Connor, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The authors found cross‐sectional evidence of self‐criticism as a mediator of the relation between childhood emotional abuse and past‐year NSSI; however, compelling methodological work indicates that cross‐sectional methods rarely reflect longitudinal mediation processes (Cole & Maxwell, ; Maxwell & Cole, ; Maxwell, Cole, & Mitchell, ). More generally, however, evidence of the overall relation between self‐criticism and NSSI has been replicated in other samples of adolescents using a variety of measures of both constructs (Baetens et al., 2014; Burke et al., ; Harkess‐Murphy, MacDonald, & Ramsay, ; Guerreiro, Figuero, Cruz, & Sampaieo, ; You & Lin, ). Other work has shown significant relations between NSSI and the related concept of low self‐esteem among adolescents (Cawood & Huprich, ; Claes, Houben, Vandereycken, Bijttebier, & Muehlenkamp, ).…”
Section: Self‐criticism Nssi and Dementioning
confidence: 96%
“…Clinicians treating patients who engage in NSSI, DE, or both behaviors should evaluate and potentially target self-critical cognitions in treatment. Compassion-focused therapy for disordered eating represents one example of such an approach, although further research is necessary to evaluate its effectiveness (Goss & Allan, 2010. Among researchers, a growing community has called for the conceptualization of direct and indirect selfharm behaviors along a spectrum driven by common processes rather than as etiologically distinct behaviors (e.g., Nock, 2010;Sansone, Levitt, & Sansone, 2003;St.…”
Section: Self-criticism As a Transdiagnostic Processmentioning
confidence: 99%
“…É de salientar que os métodos mais utilizados nestes comportamentos são as intoxicações e sobredosagens medicamentosas assim como as automutilações (Santos, 2000;Kapur et al, 2013), sendo mais frequentes no género feminino (Guerreiro et al 2014;Zetterqvist, 2015), contrastando com o comportamento suicida, que é mais relevante no género masculino (Santos, 2000;Sha er et al, 2001;Sampaio, 2009). Os comportamentos autolesivos em adolescentes são considerados um problema de saúde pública necessitados de entendimento e acompanhamento na sua complexa interação biopsicossocial, relacional e familiar devido ao seu manifesto crescimento sobretudo entre adolescentes comprometendo um desenvolvimento saudável (Trinco e Santos, 2015;Guerreiro et al, 2014;Muehlenkamp et al, 2012;Nock & Favazza, 2009). A nossa prática é concordante com os autores, assim sendo e perante esta problemática compete ao enfermeiro compreender como é que os adolescentes vivem estas situações.…”
Section: Introductionunclassified
“…Os estudos de Gmitrowlcz, et al (2014) e de Morey, et al (2008), dizem-nos que apenas 14% dos adolescentes procurou os cuidados de saúde após um comportamento autolesivo. Já para Guerreiro, et al (2014), só 13% recorreram ao hospital, essencialmente nos casos de intoxicações. Assim sendo, crê-se que seja um problema de grande relevância, carente de investigação (Cordovil.…”
Section: Introductionunclassified